TEACHING DESCRIPTIVE TEXT WRITING THROUGH PHOTOGRAPH AS A MEDIA AND GUIDED QUESTION AS A TECHNIQUE - Linarti, Hesti; Wijaya, Bambang; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research focused on teaching descriptive text writing through photograph as a media and guided question as a technique. Based on the writer’s interview to the English teacher of tenth grade students in SMA Panca Bhakti Pontianak, most of students had difficulties in writing descriptive text. The form of this research is pre-experimental study. The data had been collected by using measurement technique. The tool of data collecting was written test. The sample of this research was 30 students from Class XF. The result of this research showed that the use of photograph as a media and guided question as a technique in teaching descriptive text writing improved students’ writing ability. Students’ pre-test mean score is 54.66 and students’ post-test mean score is 76.66. Meanwhile, the effect of treatment (ES) was 1.95. Based on the result (ES > 0, 8), it was categorized as highly effective. In conclusion, the use of photograph as a media guided questions as a technique in teaching descriptive text writing to the tenth grade students of SMA Panca Bhakti Pontianak in academic year 2011/2012 is highly effective. Keywords: descriptive text writing, photograph, guided question Abstrak: Penelitian ini terfokus kepada pengajaran menulis teks deskriptif dengan foto sebagai media dan pertanyaan panduan sebagai teknik. Berdasarkan hasil wawancara penulis dengan guru Bahasa Inggris kelas 10 di SMA Panca Bhakti Pontianak, kebanyakan siswa mengalami kesulitan dalam menulis teks deskriptif. Format penelitian ini adalah Pre-Eksperimental. Data dikumpulkan melalui teknik pengukuran. Alat pengumpulan data adalah tes tertulis. Sampel penelitian adalah 30 orang siswa kelas XF. Hasil penelitian menunjukkan penggunaan foto sebagai media dan pertanyaan panduan sebagai teknik dalam pengajaran menulis teks deskriptif meningkatkan kemampuan menulis siswa. Nilai rata-rata pre-test siswa adalah 54.66 dan nilai rata-rata post-test siswa adalah 76.66. sementara itu, efek dari treatment adalah 1.95. Berdasarkan hasil (ES > 0, 8), dapat dikategorikan sangat efektif. Kesimpulannya, penggunaan foto sebagai media dan pertanyaan panduan sebagai teknik mengajar menulis teks deskriptif untuk siswa kelas 10 SMA Panca Bhakti Pontianak tahun ajaran 2011/2012 sangat efektif Kata Kunci: menulis teks deskriptif, foto, pertanyaan panduan